Risk Management Analysis on the Achievement Of Performance Indicators - Nanik Dewi Setiawati; Siti Jahroh; Dominicus Savio Priyarsono (Green Publisher Indonesia, 2025)
Control of non-communicable diseases, especially diabetes mellitus, is one of the priorities in public health programs. One of the performance indicators used to measure the success of this program is